Photostimulator allowing independent control of rods and the three cone types. - Pokorny, J; Smithson, H; Quinlan, J (2004)
This report describes a second-generation photostimulator with four primary lights that allows independent control of the stimulation of the four receptor types in the human eye. The new design uses LEDs (with light levels controlled by eight drivers that include voltage-to-frequency converters that provide 1-micros pulses at frequencies up to 250 kHz), with four center channels being combined by use of a fiber optic assembly, and likewise for four surround channels. Four fiber optic bundles are merged into a single bundle whose output is fed into a spatial homogenizer terminated by a diffuser. An interference filter is sandwiched between each LED and the fiber optic bundle. Two camera lenses collimate light from the diffusers, one for center and one for surround. The center-surround field configuration is formed by a photometric cube with a mirrored ellipse on the hypotenuse. A field lens places images of the diffusers in the plane of an artificial pupil. The fields are highly uniform. Following alignment and calibration, the center and surround fields are indistinguishable. An observer calibration procedure, designed to compensate for prereceptoral filtering, is shown by calculation to correct also for normal observer receptoral spectral sensitivity variation. With the instrument calibrated for the individual observer, a peripherally fixated 200-ms 40% contrast rod center field pulse, highly conspicuous under dark adaptation, is invisible following light adaptation.